Finite element analysis of rubber material cross specimen based on ANSYS Workbench. Issue 3 (March 2021) - Zeng, Lingqi; Zou, Huisong; Peng, Dongdong
Abstract: The finite element analysis software ANSYS Workbench was used to fit and analyze the Ogden constitutive model, and the effect of the arm seam and its parameters on the stress distribution uniformity in the central test area was simulated and analyzed. The results show that different chamfering radii and the number of arm seams have an effect on the stress distribution in the center test area of the sample. The chamfering radius of 1.5mm in the center test area has a high uniformity of uniform stress distribution and a small degree of stress concentration. As the number of arm seams increases, the uniform stress distribution in the central test area increases slightly. This study can provide a reference for the preparation of standard specimens for bidirectional tensile testing of rubber materials.